Uji Aktivitas Antibakteri Ekstrak Kulit Buah Kawista (Limonia acidissima L.) Asal Desa Pasinan, Kabupaten Pasuruan terhadap Koloni Salmonella sp. secara In Vitro - Sisca Desi Prastyaningtias; Sari Dian A.S (Pro-Life, 2023)
One of the potential agricultural products from Pasinan Village, Lekok sub-district, Pasuruan, East Java Province is Kawista Fruit. Residents of Pasinan used it for consumption, both raw and ripe. The large consumption of this fruit was caused an abundance of fruit peel. Based on the research results of phytochemical test, the extract of kawista fruit peel contains saponins, tannins, alkaloids, flavonoids, and terpenoids. Another income source of Pasinan residents comes from marine resources, that can be served in fresh fish, dried fish and other processed fish is susceptible to contaminated by microorganisms such as Salmonella sp. Salmonella sp. is pathogenic microbe lives on intestines of animals and humans. This study aims to determine the antibacterial activity of kawista peel extract on the growth of Salmonella sp. in-vitro and to determine the concentration of Kawista extract which is effective for inhibiting the growth of Salmonella sp using the paper disc diffusion method. The results of this study, the diameter of the inhibitory zone for the growth of Salmonella sp. using variables concentrations of kawista rind extract at 12.5%;25%;50%;75%;100%, with negative control are distilled water and methanol and positive control is tetracycline. At a concentration of 100% extract, the diameter of the bacterial inhibition test was the largest and significantly different from another treatment group at concentrations of 12.5%;25%;50%;75%. However, the 100% extract showed a smaller inhibitory zone than the tetracycline treatment group, but not significantly different. Based on the results of this research, it can be determined that kawista peel extract is effective for inhibited the growth of Salmonella sp. Kawista peel extract at a concentration of 100% is most effective for inhibiting the growth of Salmonella sp and shows results that are not significantly different from tetracycline. Keywords: Antibacterial, Limonia acidissima L, Salmonella sp.